Programa educativo DW Learn German para el mejoramiento de la comunicación oral en alemán en estudiantes de segundo grado de secundaria en el colegio aplicación UNAP, San Juan Bautista 2023 - Saldaña García, Marcelo (2024)
The aim of this research was to evaluate the impact of the educational program “DW Learn German” on improving oral communication in German among second-grade secondary school students at Colegio Aplicación UNAP San Juan Bautista during the year 2023. This study was characterized as evaluative type and field-based, cross-sectional, univariate, and quasi-experimental designs, incorporating both a pretest and a posttest, as well as a control group. The population and sample consisted of 73 students, divided into two groups: a control group with 36 students and an experimental group with 37. For data collection, an oral performance test that was both valid and reliable was utilized. The results indicated that the experimental group achieved a significantly higher average than the control group on a twenty-point scale (11.389 compared to 8.934). The research concluded that the implementation of the “DW Learn German” program significantly enhances oral communication in German, encompassing dimensions such as: listening comprehension, information retrieval, inference and interpretation, use of non verbal and paraverbal resources, and strategic interaction among students. This finding is supported by a p-value of 0.000, which is lower than the established significance level (α=0.05).